Manejo do solo, doses de nitrogênio e inoculação de Azospirillum brasilense em arroz de terras altas irrigado por aspersão sobre diferentes coberturas vegetais - Gitti, Douglas de Castilho [UNESP] (2015)
In order to evaluate the influence of soil management systems, nitrogen levels in coverage and seed inoculation with Azospirillum brasilense in upland rice grown after different cover crops on agronomic characteristics and rice crop production components highlands, the study was conducted during the growing seasons of 2011/12 and 2012/13 in the experimental area of the Teaching Farm and Research of the Universidade Estadual Paulista, in Selvíria (MS). The soil is of type Ferralsol epi-eutrophic Alic and clayey, originally under savannah vegetation. The average annual rainfall is 1,330 mm, the average annual temperature is 25 ° C and the relative humidity of annual mean air of 66%. The work consists of three sub-projects involving soil managements systems, nitrogen levels and presence or absence of seed inoculation with Azospirillum brasilense on the cover crops millet (subproject 1), hemp (subproject 2) and millet consortium + sunnhemp (subproject 3). It can be concluded that the dry weight of shoots of rice increased linearly with inoculation with Azospirillum brasilense seeds in function of plant cover in succession and soil management. There was a reduction in the number of panicles per m2 reduced the doses 0 and 80 kg ha-1 of nitrogen in succession to millet, and increased 120 kg ha-1 in succession to sun hemp and millet + sunnhemp. The mass of 100 grains increased by inoculation of seeds in succession to millet in the dose of 40 kg ha-1 of nitrogen. Productivity increased linearly by the greater availability of nitrogen in coverage, regardless of soil management and plant cover. In succession to millet no influence seed inoculation, however, in succession to sun hemp and millet + crotalária highest yields are obtained in the SPD and nitrogen doses of 80 and 120 kg ha-1